دراسة عملية البلعمة في المرضى المصابين بألتهاب المفاصل الرثوي و داء الذئب الأحمراري - رحمن سناء; صادق غنيمة; رحمن هناء (Al-Nahrain Journal of Science, 2010)
Phagocytotsis is one of immune responseaspects for that we study it in patients withRheumatoid Arthritis (RA) and SystematicLupus Erythematosus (SLE), these diseasesbelong to autoimmune diseases whichcharacterize with defect in immune system.We determinded phagocytic ability ofneutrophils by use suspension ofStaphylococcus aureus.The results showedsignificant decrease in phagocytic abilitypatients with R.A. compared with controlgroup (P<0.001), While in patients with SLEshowed very significant decrease comparedwith control group (P<0.001).